ANALISIS PERSEPSI DAN EKSPEKTASI MAHASISWA TERHADAP PERAN DAN FUNGSI DOSEN PEMBIMBING AKADEMIK - Intan Kumalasari (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2020)
Academic supervisors are the most appropriate resource for students to complete their education process. Supervisors canalso act as motivators, consultants and collaborators. This study aims to analyze students' perceptions and expectations ofthe role and function of academic advisors at the Poltekkes Palembang by emphasizing the dimensions of tangible,reliability, responsiveness, assurance and empathy. This study used the Importance-Performance Analysis (IPA) methodand mapped into a Cartesian diagram. Measuring the overall level of student satisfaction was using the CustomerSatisfaction Index (CSI). The sample of this research was 228 Poltekkes Palembang students who were selected usingproportional stratified random sampling technique. Data collection was using a questionnaire sheet with a Likert scaleand analyzed using analysis of the level of interest and customer satisfaction. The statistical test showed that the attributethat has the most satisfactory performance was the appearance of the academic supervisor with a mean of 3.28, while theattributes that need to be prioritized for improvement were special attention to individual students with a mean of 2.42.Through the calculation of CSI, the value was 73.7% (0.66-0.80). This shows that the index of student satisfaction with therole and function of academic advisers was in satisfactory criteria. The performance of lecturers as academic advisersmust be improved and become a lecturer 's attention, especially in several attributes, namely the closeness of therelationship, attention to student difficulties, providing information, and monitoring student academic development.Keywords: academic supervisor, perception, student expectation.